KAJIAN DESAIN KARAKTER PADA BUKU “HERITAGE OF EAST JAVA” SEBAGAI DAYA TARIK VISUAL - Victor Adiluhung Abednego; Yudhistya Ayu Kusumawati (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2019)
Tourism in East Java has a huge potential and need to be introduced to the wider community. To increase the user knowledge about tourism potential, we need media that can be utilized and can be reached by all groups. Illustration book is one of alternative media that can be applied. Books are media that can be interesting for children, especially because they are equipped with interesting illustrations, the using of bright color and the cuteness of character design. The use of character designs in this illustration book is a visual attraction. This research method uses descriptive qualitative method explains the character study in terms of several aspects, including iconic characters, the use of colors, the cuteness aspects of character design. This study produced a character design plan that was applied to the Heritage of East Java illustration book on the introduction of local culture in East Java. It is expected that the existence of character designs can facilitate the conveying of messages to users other than that it is expected to increase user knowledge of tourism in East Java